Analisis Faktor-Faktor yang Mempengaruhi Kualitas Informasi Laporan Keuangan Pemerintah Daerah (Studi Kasus pada SKPD di Kabupaten Indragiri Hilir) - Herda Nengsy; Sarimaulina Sarimaulina (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2019)
This study aims to determine and empirically test the factors that influence the quality of information on the financial statements of local governments in Indragiri Hilir Regency, namely the influence of human resources, utilization of information technology and internal control systems. The population in this study is the apparatus / staff of the financial department that carries out the accounting and management functions of the Regional Government Financial Statements. The sampling technique is done by using the Purposive Sampling method with the apparatus / staff criteria of the finance department that carries out the function of accounting and financial statement management with a work duration of more than one year with 93 respondents. The technique of data collection is done by survey method by distributing questionnaires directly to respondents. This study uses multiple linear regression data analysis methods with the results of human resource research affect the quality of information Indragiri Hilir district government financial report, the use of information technology does not affect the quality of information Indragiri Hilir Regional Government Financial Report, and the internal control system affects the quality information on Indragiri Hilir District Government Financial Statements.